1997
DOI: 10.2508/chikusan.68.273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture Content and Different Levels of Additives on Chemical Composition and in vitro Dry Matter Digestibility of Rice Straw

Abstract: The effects of additives and a combination of alkaline or enzyme treatment with that of a nitrogenous compound on improvement for the utilization of rice straw by ruminants were determined.In experiment 1, rice straw of ca 500g dry matter (DM) each was treated with sodium hydroxide (NaOH), calcium hydroxide (Ca(OH)2), urea, ammonia, NaOH+urea, Ca(OH)2+ urea, and cellulolytic enzymes such as clampzyme and cellulase with or without urea adjusting the DM level to 65% or 80% and the effect on the chemical composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…It has been well documented that ammonia treatment of forage improves its digestibility and its nutritive value (Buettner et al, 1982;Orden et al, 2000). The improvement of DM degradation for UCS in the present study is comparable to what was reported for 3% urea-treated wheat straw (Sirohi and Rai, 1999) and for 4% calcium hydroxide treated straw (Pradhan et al, 1997). The results of the present study show that ammonia treatment is promising for the improvement of low quality forage such as rice straw.…”
Section: Discussionsupporting
confidence: 87%
“…It has been well documented that ammonia treatment of forage improves its digestibility and its nutritive value (Buettner et al, 1982;Orden et al, 2000). The improvement of DM degradation for UCS in the present study is comparable to what was reported for 3% urea-treated wheat straw (Sirohi and Rai, 1999) and for 4% calcium hydroxide treated straw (Pradhan et al, 1997). The results of the present study show that ammonia treatment is promising for the improvement of low quality forage such as rice straw.…”
Section: Discussionsupporting
confidence: 87%
“…In the past, numerous investigations involving urea treatment of rice straw, with or without additional supplementation, were performed not only in the laboratory (Reddy, 1996;Shen et al, 1998;Vadiveloo, 2003) but also in field trials (Prasad et al, 1998;Vu et al, 1999;Akter et al, 2004). Pradhan et al (1997) showed that addition of Ca(OH) 2 to urea improved the IVDMD. Sirohi and Rai (1995) demonstrated that a combination of 3% urea plus 4% lime at 50% moisture for 3 weeks incubation time was the most effective treatment for improving degradability of rice straw.…”
Section: Chemical Treatmentmentioning
confidence: 99%
“…Lime treatment : Lime (CaO/Ca(OH) 2 ) is a weak alkali agent with a low solubility in water. It has been reported that lime can be used to improve the utilization of straw and also can be used to supplement the ration with calcium, which has been found to be in a negative balance in cattle fed only rice straw (Hadjipanayiotou, 1984;Pradhan et al, 1997;Chaudhry, 1998). Soaking and ensiling are two methods of treating straw with lime.…”
Section: Chemical Treatmentmentioning
confidence: 99%
“…On the other hand, calcium hydroxide is a weak alkali agent with a low solubility in water. It has been reported that calcium hydroxide can be used to improve the utilization of straw and also can be used to supplement the ration with calcium, which has been found to be in a negative balance in cattle fed only rice straw (Hadjipanayiotou, 1984;Pradhan et al, 1997;Chaudhry, 1998). It was suggested that a combination of lime and urea would give better results than urea or lime alone.…”
Section: Chemical Composition Of Feedmentioning
confidence: 99%